Faktor-Faktor Yang Mempengaruhi KepuasanPemakai Akhir Sistem Informasi Akuntansi(Studi Empiris Pada Bank Perkreditan Rakyat Di Kota Surakarta) - Ulfah, Alfiani; , Dr. Noer Sasongko, SE, M.Si, Ak (2016)
This research aims to investigate the factors that influence the satisfaction of end users of accounting information systems, in particular the employees of Rural Banks in Surakarta. The variables used in this research are: the dependent variable, that is the satisfaction of end users of accounting information systems, while the independent variables used are Content, Accurate, Forms, User Ease and accuracy of the Time. The sample in this research were the employees of Rural Banks in Surakarta who use an accounting information systems and willing to became a respondents. The method of collecting samples used in this research is purposive sampling with 56 samples. The data used in this research is primary data using questionnaires, and multiple linear regression as data analysis technique. The result shows that the significant level of 0,05 from Content, Accurate, Forms, User Ease and accuracy of Time influence the satisfaction of end users of accounting information systems.